Labour market institutions and macroeconomic shocks - Yu-Fu Chen; Dennis J. Snower; Zoega Gylfi (Centre for Economic Policy Research (CEPR), 2002)
Macroeconomic shocks and labour-market institutions jointly determine employment growth and economic performance. The effect of shocks depends on the nature of these institutions, and the effect of institutional change depends on the macroeconomic environment. It follows that a given set of institutions may be appropriate in one epoch and not in another. We derive a dynamic model of labour demand in which the effect of firing costs on labour demand depends on the macroeconomic environment: when the level of macroeconomic activity is expected to drop and/or the trend rate of productivity growth is small, a rise in firing costs affects mainly (and adversely) the hiring decision and not the layoff decision. This makes firing costs harmful to employment when it may appear most appropriate. In contrast, firing costs can raise employment during periods of high growth and positive shocks. Our hypothesis is supported by empirical results using OECD data.
Keywords: E32; J23; J24; J54; 330; Arbeitsmarkttheorie; Schock; Arbeitsmarktflexibilisierung; Kündigung; Theorie